Audit Quality: The impact of Auditors' Competence, Independence, and Ethics: Study of Government Agencies in West Java - Galih Putra Prawiranegara (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
The demands of society on governance for the realization of good and clean governance are increasing which requires government officials to be competent in carrying out the internal control function. In regional government, the supervisory function is the duty of the Inspectorate of Province. The purpose of an audit process is to produce a quality audit, which can be influenced by several factors including competence, independence, and ethics of the auditors. This study is conducted on auditors in the Inspectorate of West Java Province with a total of 85 auditors with descriptive research methods and verification of quantitative approaches. Primary data collection using a questionnaire. This study used multiple linear regression analysis for the data analysis technique. The purpose of this study was to determine the influence of competence, independence, and ethics on audit quality in the Inspectorate of West Java Province. The results of this research show that competence, independence, and ethics has an influence on quality audits both partially and simultaneously. Competense, independence, and ethics each have a positive and very strong level of relationship to audit quality.